Application of functionalized ether in lithium ion batteries. Issue 85 (27th November 2017) - Hu, Fang; Song, Taeseup
Abstract : Functionalized ethers have been explored to improve the electrochemical properties of lithium ion batteries (LIBs). Abstract : Ethers can be typically categorized as chain ethers, aromatic ethers and crown ethers. Compounds with ether groups play an important role in chemistry, biology and functional materials. Ether acts as an anesthetic in medicine, and crown ethers are used to construct mechanically interlocked molecules. Lithium ion batteries are becoming more and more important in our modern life as our mobile devices such as smart phones and laptop computers need power supplies. In recent years, the ethers have been explored to improve the electrochemical properties of lithium ion batteries. Depending on the function of the ether groups, they are widely used as electrolytes, additives, binders, separators or anodes. In this paper, we review the progress that has been made in the use of functionalized ethers in lithium ion batteries and the synthesis strategies for them, and present the future research direction of functionalized ethers in lithium ion batteries.